Propuesta de mejora en la cadena de suministros en la importadora Az Solution International S.A.S. de Cartagena de Indias D.T. Y C. (2021)
The process in the supply chain is fundamental for competitiveness and agility in storage and dispatch times. Therefore, this degree project presents a proposal to improve the supply chain of the company Az Solution International SAS in the city of Cartagena de Indias D.T. y C.